Shocks and Government Beliefs: The Rise and Fall of American Inflation - Sargent, Thomas; Williams, Noah; Zha, Tao (American Economic Review, 2006)
We use a Bayesian Markov Chain Monte Carlo algorithm to estimate a model that allows temporary gaps between a true expectational Phillips curve and the monetary authority's approximating nonexpectational Phillips curve.A dynamic programming problem implies that the monetary authority's inflation target evolves as its estimated Phillips curve moves.Our estimates attribute the rise and fall of post WWII inflation in the US to an intricate interaction between the monetary authority's beliefs and economic shocks.Shocks in the 1970s altered the monetary authority's estimates and made it misperceive the tradeoff between inflation and unemployment.That caused a sharp rise in inflation in the 1970s.Our estimates say that policymakers updated their beliefs continuously.By the 1980s,